Heat transfer effects during cold dense gas dispersion - Meroney, Robert N., author; Neff, D. E., author; Andreiev, G., author; Fluid Mechanics and Wind Engineering Program, Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1983)
Wind tunnel concentration data were obtained for continuous area releases of isothermal, cold N2, cold CO2 and cold CH4 clouds. Wind tunnel results were compared to field test results and to a computer model simulation. Heat transfer and humidity effects on model concentration distributions were significant for methane plumes when surface Richardson numbers, Rix, were large (i.e. low wind speed and high boiloff rates conditions). At field scales heat transfer and humidity still play a role in the dispersion of methane spill cases, but plume dilution and lift off are not as exaggerated as for the-model cases.
Final report.
November 1983.
CER83-84-GA-DEN-RNM3.
GRI-83-0082.
Keywords: Wind tunnel models; Liquefied natural gas; Heat -- Transmission; Humidity